Analysis of China’s marine economic policy: regional policy characteristics, evolution and assessment - Shen, Chuyi; Yang, Zhenjie; Zhan, Jinghui (Frontiers in Marine Science, 2025)
IntroductionThe transition towards a sustainable blue economy (SBE) is a crucial component of global marine economic governance. This study examines the evolution of China’s marine economy policies and their role in facilitating this transition.MethodThrough a systematic review of 40 national policy texts from 2000 to 2023, this study uses content analysis and social network analysis to conduct a multidimensional empirical analysis. We analyze policy development trends, thematic priorities, and structural characteristics across China’s three major marine economic zones– the Northern Marine Economic Zone (Liaoning, Hebei, Tianjin, Shandong), Eastern Marine Economic Zone (Jiangsu, Zhejiang, Shanghai), and Southern Marine Economic Zone (Fujian, Guangdong, Hainan, Guangxi). These zones were chosen due to their distinct economic profiles, resource endowments, and roles in national marine strategies.ResultThe research findings are as follows: 1. Policy evolution occurred in three phases: rapid economic growth (2003–2010), integration of economy and environment (2011–2018), and sustainable development (2019–2023), though economic objectives remain dominant. 2. A pronounced imbalance in policy tools: environmental tools (42.18%) were most frequent, followed by supply-oriented (37.30%) and demand-oriented tools (20.52%). 3. Regional disparities: Northern zones (politically closer to the central government) prioritized supply-oriented tools (e.g., infrastructure funding), while Southern and Eastern zones emphasized environmental tools (e.g., regulations) .DiscussionThe study concludes that China’s policy framework still prioritizes industrial growth over ecological balance. To advance SBE, policymakers must rebalance tool usage, and tailor strategies to regional contexts.